The Effects of Expectation Disconfirmations on Customer Outcomes in E-Markets: Impact of National Culture. Issue 4 (1st October 2016) - Song, Lei; Weisstein, Fei L.; Anderson, Rolph E.; Swaminathan, Srinivasan; Wu, Gavin Jiayun; Feng, Shan; Tan, Kang (Frank)
Abstract : Prior research has shown that after receiving online services of varying quality, customer expectations are either positively disconfirmed (i.e., services exceed customer expectations) or negatively disconfirmed (i.e., services fall short of customer expectations). The present research examines expectation disconfirmation across national cultures and its subsequent impacts on e-word-of-mouth, e-satisfaction, and e-loyalty. The results show that Chinese customers are more tolerant of e-services that result in negative disconfirmations, although online shoppers from the United States are more likely to be loyal or generate positive e-word-of-mouth when experiencing positive disconfirmations. Suggestions for adjusting multinational e-tailers' strategies to better serve customers across national cultures are discussed.